Estudio de prefactibilidad para la instalación de una planta de producción de sidra a partir de manzana delicia con miel de abeja - Cordova Mendez, Allison Marisol (2020)
This pre-feasibility study will analyze the commercial, technical and economic viability of implementing a plant for the production of cider from "manzana Delicia" and honey in Peru. The product in mention is obtained through the fermentation of apple juice and bee honey, with a semi-sweet and slightly carbonated flavor in a 330 ml presentation. It results attractive due to the growth in format of beverages "ready to drink" and as excellent alternative since it is free of gluten. Market studies were conducted and consumption patterns were analyzed, which allowed a psychographic segmentation of the market, establishing a target audience that belongs to the NSE A and B of Metropolitan Lima in the age range between 18-60 years. After defining the commercial viability, a technical investigation was performed which determined, by means of location analysis, that the district of Lurin is the most suitable for the location of the plant. For this purpose, critical factors were established and a factor ranking was carried out at macro level (provinces) and micro level (districts). The size of the market is the limitation of the project with 438,302 liters of cider per year. With such information, the analysis on the engineering required by the project was made, by which it was determined that the necessary area for the plant is of 718m2 and 17 collaborators are needed. Finally, the economic, financial and social viability of the pre-feasibility study was determined, concluding that the project would be profitable, obtaining in the economic evaluation a NPV of S/ 3,091,171, an IRR of 57% and a recovery period of 3.53 years. On the other hand, the financial evaluation obtained a NPV of S/ 3,619,072, an IRR of 74% and a recovery period of 2.86 years.